Cultural ergonomics - Kaplan, Michael, 1962- (Emerald, 2004)
In work environments world-wide, whether simple or complex, the ways in which people think, do their jobs, and interface with other human beings grow out of their experiences in the groups of which they are or have been a part. How these influences affect their performance and human interfacing in work environments throughout the world is the subject of cultural ergonomics. In this volume, distinguished scientists explore these cultural influences in relation to significant current concerns of ergonomics and human factors. These include scientific-philosophical considerations, aircraft safety, maritime safety, cross-national training, effective use of the world-wide web, multinational decision making, third-world industrial development, implementation of technology transfer, and the functioning of multicultural teams.
Keywords: Human engineering.; Cognitive science.; Human-machine systems.; elektronické knihy; electronic books